Poor COVID-19 Preventive Practice among Healthcare Workers in Northwest Ethiopia, 2020. (20th October 2020) - Kassie, Belayneh Ayanaw; Adane, Aynishet; Abebe Kassahun, Eskeziaw; Ayele, Amare Simegn; Kassahun Belew, Aysheshim
Abstract : Background . The novel coronavirus disease (COVID-19) pandemic outbreak affects the global social, economic, and political context and becomes a significant threat to healthcare providers who are among the exposed groups to acquire and transmit the disease while caring and treating patients. It is crucial to comply with prevention recommendations so as to stay safe and protected. Therefore, this study aimed to assess COVID-19 preventive practice and associated factors among healthcare workers in Northwest Ethiopia. Methods . An institution-based cross-sectional study was conducted among 630 healthcare workers in Northwest Ethiopia from March to April 2020. A multistage sampling technique was used to select study participants. A pretested and structured self-administered questionnaire was used to collect data. The data were entered using Epi Info 7 and analyzed using STATA 16 statistical software. Both bivariate and multivariable logistic regression analyses were employed to identify associated factors. Adjusted odds ratio (AOR) with 95% confidence interval was used to determine independent predictors of COVID-19 preventive practice. In multivariable analysis, a variable with a P value of less than 0.05 was considered as statically significant. Result . Among 630 healthcare workers participated in the study, the overall good preventive practice towards COVID-19 was found to be 38.73% (95% CI: 34.8, 42.5). Being a male healthcare provider (AOR = 1.48; 95% CI: 1.02, 2.10), having work experience of 6–10 years (AOR = 2.22; 95% CI: 1.23, 4.00), and having poor attitude towards COVID-19 (AOR = 2.22; 95% CI: 1.03, 2.22) were found to be significantly associated with poor COVID-19 preventive practice among healthcare workers. Conclusion . Overall compliance towards COVID-19 preventive practice among healthcare workers was found to be low. Multiple education and training platforms with focus on COVID-19 preventive measures and adequate personal protective equipment and supplies should be provided for healthcare providers.